Histopathological Diagnosis of Ovarian Fibroma in a 50-Year-Old Woman - SE Salehi Dehno; K Rouzbehi; Z Asadi Kalameh; Z Salehpour (Armaghane Danesh Bimonthly Journal, 2025)
Background & aim: Ovarian fibroma is the most common solid ovarian tumor that is rarely associated with Myegs syndrome. Patients usually present with abdominal discomfort, and there have been no reports of associated groin pain. X-ray imaging and laboratory data are used for initial diagnosis. The common treatment is removal of the tumor via laparotomy or laparoscopy. Therefore, the aim of the present study was to determine and histopathologically diagnose ovarian fibroma in a 50-year-old woman.